SYNTHESIS AND CHARACTERIZATION OF CATECHIIN LOADED NANOPARTICLES AND THEIR EVALUATION FOR ANTIMUTAGENIC ACTIVITY AGAINST S. TYPHIMURIUM STRAINS - Arasoglu, Tulin; Turkoglu, Burcu; Akmayan, Ilkgul; Mansuroglu, Banu; Derman, Serap (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
To increase the bioavailability of catechin decreasing by low stability at high oxygen; pH and temperature conditions, in this study, the synthesis and characterization of catechin PLGA nanoparticles with the help of techniques of nanoencapsulation was realized and their antigenotoxic potential was evaluated. The catechin nanoparticles were prepared using poly(lactide-co-glycolide) as carrier molecule with double emulsion solvent evaporation method. Morphology and physicochemical properties of the nanoparticles were investigated by SEM, DLS and FTIR. The antimutagenic activity of catechin NPs evaluated by colorimetric analysis with AMES (MPF) assay using S. typhimurium strains against the 2-nitrofluorene. 4-nitroquinalone-N-oxide and 2-amino-anthracene mutagens in the presence or absence of S9 system. The catechin NPs has spherical shape-uniform size distribution (PDI; 0.081 +/- 0.017) with an average size of 181.7 +/- 1.387 nm, zeta potential of -18.7 +/- 0.473 mV, encapsulation efficiency of 22.04%, and drug loading of 10.46%. The antimutagenic effect of catechin and catechin NPs was not detected at the applied concentrations on both strains with and without S9, due to the low drug loading. Our study has shown that the drug loading capacity is an important parameter to achieve the desired therapeutic effect of nanoparticular system.
Keywords: Anlimutagenite; catechin nanopartiele; AMES assay; PL GA; nanoencapsulation; PLGA NANOPARTICLES; PHIP MUTAGENICITY; TEA POLYPHENOLS; ANTIOXIDANT; GREEN; INHIBITION; BLACK; PROLIFERATION; THEAFLAVINS; EXTRACTS; Environmental Sciences & Ecology